2012
DOI: 10.1063/1.4737904
|View full text |Cite
|
Sign up to set email alerts
|

On the link between electroluminescence, gate current leakage, and surface defects in AlGaN/GaN high electron mobility transistors upon off-state stress

Abstract: The degradation of AlGaN/GaN high electron mobility transistors after off-state stress is studied by means of electroluminescence (EL) analysis, gate leakage current (Ig) monitoring, and atomic force microscopy (AFM) mapping of the semiconductor surface. It is found that the degradation of Ig upon stress is due to the combined effect of the individual defects underlying each of the EL spots, which contribute a few μA each to the total Ig. After removal of contacts and passivation, a direct one-to-one correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] Several mechanisms have been postulated to explain the various degradation patterns that have been observed. [8][9][10][11][12][13][14][15][16][17][18] Several studies [19][20][21][22][23][24][25] have shown the appearance of prominent physical damage (dimples, grooves, pits, trenches, and cracks) on the semiconductor surface under the edge of the gate after prolonged OFF-state stress. The damage extends through the GaN cap and the AlGaN barrier layer and in some extreme cases reaches into the GaN buffer layer.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Several mechanisms have been postulated to explain the various degradation patterns that have been observed. [8][9][10][11][12][13][14][15][16][17][18] Several studies [19][20][21][22][23][24][25] have shown the appearance of prominent physical damage (dimples, grooves, pits, trenches, and cracks) on the semiconductor surface under the edge of the gate after prolonged OFF-state stress. The damage extends through the GaN cap and the AlGaN barrier layer and in some extreme cases reaches into the GaN buffer layer.…”
Section: Introductionmentioning
confidence: 99%
“…These EL emission points are associated with the formation of highly localized current leakage pathways, electrically shorting the gate to the 2DEG through the AlGaN barrier. 8,17 These emission regions are expected to be much smaller than the EL emission wavelength and are confined to the 2DEG at the AlGaN/GaN interface. Off state EL emission is therefore optimal for evaluating the lateral resolution of the SIL.…”
Section: A Electroluminescence Microscopymentioning
confidence: 99%
“…EL emission is observed at the drain edge of the gate in the standard microscope image, where the electric field is located. 8,9,17 However, identification of the exact location of the emission is lacking due to the finite spatial resolution, which is ~750 nm around the peak detected EL emission wavelength of 700-800 nm. Figure 5(b) shows the SIL-enhanced EL image, individual EL emission spots are clearly resolved and can be unambiguously located, exactly at the gate edge where the peak electric field is predicted.…”
Section: A Electroluminescence Microscopymentioning
confidence: 99%
See 2 more Smart Citations